THE RELATIONSHIP OF FINANCIAL INNOVATION AND ECONOMIC GROWTH: TURKEY CASE - Gülay Çizgici Akyüz; Seval Akbulut Bekar (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
ABSTRACTThe aim of this study is to research the relationship between financial innovation and economic growth during the 1970–2019 period in Turkey’s economy. Here, GDP per capita is used as an indicator of economic growth, GDP ratio of domestic credits to private sector and the ratio of broad/narrow money supply as indicators of financial innovation, and GDP ratio of gross fixed capital formation as an indicator of financial growth. The relationship between financial innovation and economic growth is analyzed by means of Dolado-Lüthkepol and ARDL methods. Findings reveal that financial innovation and development had an impact on growth in Turkey’s economy during the 1970–2019 period. It has been established that the GDP ratio of private sector loans, used as an indicator of financial innovation, and GDP ratio of gross fixed capital formation, used as an indicator of financial development, have a positive effect on growth. On the other hand, it has been determined that the effect of the variable broad money supply/narrow money supply, which is used as an indicator of financial innovation, on growth is negative. Accordingly, it has been determined that financial innovation has positive and negative effects on Turkey’s economy